TA’TSIRU TORIQOH “COURSE RIVIEW HORAY “FI TA’LIM MUFRODAT DURUS LUGOH LI THALIBAT SHOF AL AWWAL (MA’HAD RIYADLUL ‘ULUM CONDONG TASIKMALAYA): Pengaruh Penggunaan Metode Course Riview Horay dalam Pembelajaran Kosakata Bahasa Arab Untuk Siswi Kelas 1 SMP (Pondok Pesantren Riyadul 'Ulum Condong) - Masruroh, Emas; Fauziah, Gina (Jazirah: Jurnal Peradaban dan Kebudayaan, 2023)
Riyadlul Ulum Wadda'wah Islamic Boarding School is one of the integrated boarding schools that teaches language lessons, one of which is Arabic lessons, where Arabic is the official language used in the teaching and learning process as well as in daily speaking. One of the challenges that is still a problem today is that students have difficulty memorizing Arabic vocabulary. Course review horay is a method that can be used by teachers to overcome the problems of students' difficulties in memorizing Arabic vocabulary in first grade of KMI.This study aims to empirically examine the effect of the course review horay method on students' ability to memorize and Arabic vocabulary in durusul lughoh lessons.the researcher uses a quantitative research method in which the data to be obtained are in the form of numbers and analysis using statistics, the data collection technique is carried out by the test method to obtain information on the understanding of KMI class 1 regarding Arabic language learning using the course review horay method and did not use the Horay course review method. The analysis technique used is descriptive analysis technique, normality test, homogeneity test and hypothesis testing. The population in this study were first grade students of the Riyadlul ulum wadda'wah Islamic boarding school, amounting to 357, while the sample used was 15% of the existing population, namely 53.55 rounded to 54 students.The results of this study indicate that the application of the course review horay method significantly positively affects. This is proven by the significant increase in the value of the comparison of the difference between the pretest and posttest scores after the course review horay research program was implemented. Therefore, the course review horay method can be said to be able to facilitate students in memorizing vocabulary (durusul lughoh).